2015
DOI: 10.1586/17434440.2015.1100071
|View full text |Cite
|
Sign up to set email alerts
|

Stand-alone interspinous spacer versus decompressive laminectomy for treatment of lumbar spinal stenosis

Abstract: Both treatments provide effective and durable symptom relief of claudicant symptoms. This stand-alone interspinous spacer offers the patient a minimally invasive option with less surgical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Lauryssen et al [17] documented consistently similar clinical improvements in back and leg pain, back function, and condition-specific impairment for both the Superion and decompressive laminectomy at 2 years postoperatively. Herein, we found robust effect sizes (>1.0) at each postoperative follow-up interval for ODI and ZCQ with Superion treatment, uniformly higher than comparable effect sizes with laminectomy, and the magnitude of the effect size was durable through 4 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Lauryssen et al [17] documented consistently similar clinical improvements in back and leg pain, back function, and condition-specific impairment for both the Superion and decompressive laminectomy at 2 years postoperatively. Herein, we found robust effect sizes (>1.0) at each postoperative follow-up interval for ODI and ZCQ with Superion treatment, uniformly higher than comparable effect sizes with laminectomy, and the magnitude of the effect size was durable through 4 years of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to the X-STOP spacer with large surgical exposure, the minimally invasive nature of the Superion spacer contributes to smaller blood loss, less operative time, and shorter hospitalization. In addition to its small incision, the Superion procedure avoids generating large scar tissue around symptomatic levels which may reduce the intricacy of future revision, removal, or further decompression surgery [ 24 ]. The data from previous 2-year follow-up studies suggested that both DI and the Superion procedure provide effective and durable symptom relief of claudication symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Lauryssen et al published a review article in 2015 comparing the results of the IDE trial to a compilation of 19 published studies on the use of decompressive laminectomy for the treatment of LSS. 88 The article compared back and leg pain, ODI score, and ZCQ score between those in the IDE study treated with ISS and the published results for patients treated with laminectomy. The percentage improvements at 24 months uniformly favored those treated with ISS compared to baseline scores.…”
Section: Interspinous Spacers For Indirect Lumbar Decompressionmentioning
confidence: 99%